Development of interactive multimedia CD in learning year one Mathematics / Athniah Izuddin - Izuddin, Athniah (2005)
Multimedia technology has thus been the base of the development of courseware especially in aiding teaching and learning. Teachers act as a facilitator while the students build their knowledge from the information acquired based on what they had learned. By infusing the many elements of multimedia, such as text, graphics, audio, animation and interactivity helps the students understand the certain subject further. The approach used in the application is repetitive which helps the student to memorize and be able to master the subject better. The project aims to develop a supplement material for the National School Syllabus in learning Mathematics for Year One pupil aged seven years old. The development of the software is based on the Instructional Design Methodology, the ADDIE model which is the acronym for Analyze. Design, Develop, Implement and Evaluate. The research framework is based on Robert M. Gagne's learning theory which is the Conditions of Learning. There are basically three main modules, which are Numliers. Addition and Subtraction. With the development of this software, children will be able to have fun while learning and enhancing their mathematical skills with the games provided. The games itself have their own purpose and objective, among them are to boost the student knowledge and to encourage quick thinking in solving mathematical equation.